Bernier / Eliades Gallery 1999-2009 : Jean Bernier - Marina Eliades Gallery / Agra publications. - Colombo, Paolo; Koroxenidis, Alexandra; Bernier / Eliades Gallery, Athene (Athene : Bernier / Eliades Gallery Athene, 2010)
Bernier / Eliades Gallery Athene ; Akakce, Haluk ; Baldessari, John ; Braeckman, Dirk ; Brandl, Herbert ; Caccavale, Giuseppe ; Casebere, James ; Charlton, Alan ; Cragg, Tony (Anthony) ; Estève, Lionel ; Van Genderen, Monique ; Gilbert & George ; Hadjimichalis, George ; Van Imschoot, Jan ; Jamie, Cameron ; Kavallieratos, Takis & Stella ; Langa, Moshekwa ; Lappas, George ; Long, Richard ; Morley, Ivan ; Muñoz, Juan ; Navridis, Nikos ; Oehlen, Albert ; Ogland, Ylva ; Oursler, Tony ; Poitevin, Eric ; Richter, Daniel ; Rocklen, Ry ; Rothenberg, Susan ; Ruby, Sterling ; Rückriem, Ulrich ; Ruscha, Ed ; Sandison, Charles ; Schütte, Thomas ; Shaw, Jim ; Soulou, Christiana ; Trivier, Mark ; Vallance, Jeffrey ; Webb, Boyd ; Weber, Marnie ; West, Franz ; Williams, Sue ; Wilson, Jane & Louise ; Wilson, Robert ; Yan Pei-Ming ; Zacharopoulou, Katerina
Engels
Grieks
boek